The US New Imperialist Trend through the Mass Destruction Weapons Imposture in Iraq after the September 11th Attacks - Boutiba, khadidja; kabache, Taieb (University of Ammar Theledji -Laghouat, 2021)
The September eleventh attacks contributed to shaping the American neo-imperialism in the world. The hijackers are Arabs who made the region vulnerable to unjust American imperialism. The Bush Doctrine and his agenda in the Middle East were in favor of the war on terror. It included using military forces in Iraq and taking down Saddam Hussein’s regime, Iraq's ideology, education, and even culture. Iraq and other Arab countries are oil-rich countries; such a fact made them a field of colonial ambitions since ages. This study aims to show the imperial actions of the U.S. in Iraq after the 9/11 attacks. It sheds light on the pretexts that were given by the Bush administration to invade Iraq and revealing the real causes of the occupation. America has accused Iraq of involvement in terrorism attacks and having mass destruction weapons, but none of those allegations have been proven. America's invasion of Iraq and the use of military forces were therefore unjustified, but rather to achieve colonial ambitions boosted by economic impulses. As a matter of fact, America has pursued different imperialist policies in the rest of other countries according to its relations with the country and the extent to which it is threatened or paved for its interests in the Middle East. In this research the approaches that used are the historical and descriptive approaches in order to depict American new imperialism in the Middle East and to shed the light on the real goals of US in Iraq. This research resulted in discovering the strategies and the pretexts of US and its hidden intentions in the Middle East and the real motives to invade Iraq